Optimal frequency of platelet-rich plasma injections for managing osteoarthritis: A longitudinal study - Masahiko Kemmochi (Regenerative Therapy)
Introduction: Recent reviews suggest that PRP injections can improve pain and function more effectively than other treatments; however, consensus on the optimal number of injections is lacking. We aimed to determine the optimal administration frequency and number of PRP injections for management of osteoarthritis (OA) symptoms, to examine long-term effects and structural improvements with PRP, and to determine correlations between clinical outcomes and imaging findings. Methods: This longitudinal study included 167 patients with knee OA, categorized using the Kellgren–Lawrence (KL) grading system. Participants received up to six PRP injections and were followed-up for 24 months. Pain levels were assessed using the visual analog scale (VAS); functional recovery was measured using the Knee Injury and Osteoarthritis Outcome Score (KOOS). To determine whether PRP can induce sustained structural improvements, we used the MRI Osteoarthritis Knee Score (MOAKS) to monitor changes in bone-marrow lesions (BMLs). Data were analyzed using repeated-measures analysis of variance to identify significant changes in pain and functional outcomes. Results: VAS and KOOS scores significantly improved after PRP treatment. Patients with KL grades 1 and 2 exhibited maximum pain relief after the fourth injection; those with KL grades 3 and 4 showed optimal results after the fifth injection. Improvements were maintained or enhanced at the 24-month follow-up. The effect size increased as the number of treatments progressed, and especially after the fourth treatment, with a Cohen's d values of −1.22, −1.28, and −0.99 (p < 0.0001). Conclusions: PRP injections administered at specific intervals can significantly reduce pain and improve function in patients with OA, with the required frequency depending on disease severity. These findings support the customization of PRP-treatment protocols based on individual patient profiles to maximize therapeutic benefits. Trial registration: This study has been registered with the clinical trial register of the Japan Medical Association Center for Clinical Trials (JMA-IIA00351). Unblinded study registration: This study has been registered with the clinical trial register of the Japan Medical Association Center for Clinical Trials (JMA-IIA00351). Level of evidence: II.